2022
DOI: 10.3390/jpm12071032
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Kidney Damage Associated with Tobacco Use: Preventive Application

Abstract: Although long-term smoking has been associated with chronic kidney disease, its effect on kidney function in early stages has not been clarified. Therefore, the proposed objectives were: (1) to identify subclinical kidney damage in smokers, through a panel of biomarkers; (2) to evaluate the progression of subclinical kidney damage after two years of consumption in these patients; and (3) study whether quitting smoking reduces kidney damage. A prospective study was carried out (patients recruited from a primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Furthermore, smoking has an impact on CKD progression in patients [ 77 , 78 ], especially diagnosed with renal deterioration [ 79 ]. High glomerular filtration rate and greater prevalence of proteinuria in smokers suggests a hyperfiltration mechanism.…”
Section: Factors That May Be Deeply Related To Kidney Agingmentioning
confidence: 99%
“…Furthermore, smoking has an impact on CKD progression in patients [ 77 , 78 ], especially diagnosed with renal deterioration [ 79 ]. High glomerular filtration rate and greater prevalence of proteinuria in smokers suggests a hyperfiltration mechanism.…”
Section: Factors That May Be Deeply Related To Kidney Agingmentioning
confidence: 99%
“…Tascón et al's (2022) study confirmed the effect of smoking on urinary albumin/protein excretion in persons from the general population with known normal renal functions also concluded that the albuminuria excretion rate was in correlation with the number of daily cigarettes smoking (measured as cotinine excretion). 19 …”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle choices and habits have a substantial influence on the development of CKD. The paper "Early Diagnosis of Kidney Damage Associated with Tobacco Use: Preventive Application" accentuates a direct relationship between smoking and early subclinical kidney damage [7]. Significantly, the study has identified a panel of biomarkers capable of detecting this condition, including Neutrophil gelatinase-associated lipocalin, Kidney injury molecule-1, N-acetyl-beta-D-glucosaminidase, Transferrin, and Ganglioside-activating protein GM2.…”
mentioning
confidence: 99%